The epidemiological characteristics of (COVID-19), recommendations to contain the out- break in early stage and prevent the disease from getting out of control in Libya. 1 - Ben Sauod, Ekram; ALnasfi, Saud; Abuzayd, Najaw (Libyan Journal of Science &Technology, 2022)
Coronaviruses (CoVs) are a large family of viruses that cause illness ranging from mild com- mon cold to more severe diseases such as acute respiratory distress syndrome (SARS ) in China in 2003, Middle East Respiratory Syndrome (MERS) in Kingdom of Saudi Arabia (KSA) in 2012, and Coronaviruses disease 2019 (COVID-19). COVID-19 is caused by SARS- CoV-2, represent- ing a potentially fatal disease that is of great global public health concern. COVID-19 is sug- gested to be of zoonotic origin due to the exposure to the wet animal market in Wuhan City in China. Human-to-human transmission of the COVID-19 and direct contact the main mode of transmission. Therefore, the rapid spread of COVID-19 between human transmissions is a big challenge worldwide. As the disease is not completely known, the virus may take off measures by the WHO and the national CDC of Libya should be implemented to suppress the transmis- sion. Ongoing investigations worldwide are important for identifying the animal source and reservoir the disease. Currently no drugs licensed for the treatment or prevention of COVID- 19, the WHO and other health organizations should create vaccine or treatment for COVID-19. We highlight in this review article the epidemiology, mode of transmission, symptoms, and recommendations to contain the outbreak in the early stage and prevent the disease from getting out of control in Libya.